2013
DOI: 10.1002/jwmg.612
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid double-observer sightability model for aerial surveys

Abstract: Raw counts from aerial surveys make no correction for undetected animals and provide no estimate of precision with which to judge the utility of the counts. Sightability modeling and double‐observer (DO) modeling are 2 commonly used approaches to account for detection bias and to estimate precision in aerial surveys. We developed a hybrid DO sightability model (model MH) that uses the strength of each approach to overcome the weakness in the other, for aerial surveys of elk (Cervus elaphus). The hybrid approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
93
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(97 citation statements)
references
References 41 publications
3
93
1
Order By: Relevance
“…Previous research has shown that the detectability of ungulates is influenced by group size, canopy cover, individual activity (bedded, standing, moving), ground terrain, and light conditions (Thomas and Gray 2002;Gilbert and Moeller 2008;Patterson et al 2014;Peters et al 2014). Of these factors, vegetation cover, which is largely dependent on the habitat, is the most frequently reported factor known to affect the detectability of target wildlife during surveys (Gasaway 1985;Samuel et al 1987;Gilbert and Moeller 2008;McIntosh et al 2009;Jarding 2010;Griffin et al 2013). For this reason we chose to focus on the effect of habitat on the detection of targets.…”
mentioning
confidence: 99%
“…Previous research has shown that the detectability of ungulates is influenced by group size, canopy cover, individual activity (bedded, standing, moving), ground terrain, and light conditions (Thomas and Gray 2002;Gilbert and Moeller 2008;Patterson et al 2014;Peters et al 2014). Of these factors, vegetation cover, which is largely dependent on the habitat, is the most frequently reported factor known to affect the detectability of target wildlife during surveys (Gasaway 1985;Samuel et al 1987;Gilbert and Moeller 2008;McIntosh et al 2009;Jarding 2010;Griffin et al 2013). For this reason we chose to focus on the effect of habitat on the detection of targets.…”
mentioning
confidence: 99%
“…(1) A simple Lincoln-Peterson estimate (i.e., not including any covariates) based on the 2-occasion aerial observations (Graham and Bell, 1989) relies on all groups being equally likely to be seen, but the vast difference in elk group size along with other factors affecting sighting probability were expected to make this assumption implausible and resulting estimates unreliable. (2) We discuss the contrast between our methods with simple sightability models (Steinhorst and Samuel, 1989), but these offer no improvements over the other methods presented here, as has been previously argued and demonstrated empirically (see model M S in Griffin et al, 2013), so we do not present estimates based on this method.…”
Section: F -Raw Count By Front Seat Observers In the Helicoptermentioning
confidence: 77%
“…Our models M D and M H are structured similarly to models in Griffin et al (2013), which should be consulted for additional details on model structure and fitting methods. We fit these same models to alternative subsets of the data, giving rise to M D + and M H * estimates for comparison purposes.…”
Section: F -Raw Count By Front Seat Observers In the Helicoptermentioning
confidence: 99%
See 2 more Smart Citations